Aglomerações produtivas no nordeste do Brasil: análise comparativa entre os métodos de identificação e as políticas públicas - Santos, Lais Silva (2016)
The present work aims perform a critical analysis of the classification of Local Productive System (SPLs) on the northeast of Brazil in 2013, making sure that they can be considered SPLs, according to the methodology adopted by Suzigan (2006). For this goal to be achieved, we used data from RAIS/MTE 2013, covering 188 micro-regions of the northeast. From these data, were calculated locational coefficients (QL), and the locational gini-coefficients (GL), per industry class. Later, were made two more steps, the first was a non-compliance criterion application and the second was the grouping of related activities classes that can find in the same micro-region. The study concludes that the states of Sergipe, Paraíba, Rio Grande do Norte, Piauí and Alagoas, the quantity of agglomerates identified from scientific method, are lower than those who make part of the State Program of APLs (PAPL). The states of Ceará, Bahia and Pernambuco have greater amount of clusters identified by scientific method than APLs, that are supported the Government. The state of Maranhão, has the same quantity of agglomerates detected and APLs. Besides that, there is a very small quantity correspondence between clusters identified for the search and those supported by states of the Northeast. This is due to the fact that much of the APLs of program, don´t have great economic relevance in relation to the northeast, analyzing the number of jobs in this section and number of establishments.